Quercetin Attenuates Diabetic Peripheral Neuropathy by Correcting Mitochondrial Abnormality via Activation of AMPK/PGC-1α Pathway in vivo and in vitro - Zhang, Qian; Song, Wei; Zhao, Bingjia; Xie, Jun; Sun, Qing; Shi, Xiaohu; Yan, Bin; Tian, Guoqing; Liang, Xiaochun (Frontiers in Neuroscience, 2021)
The AMPK/PGC-1α pathway mediated mitochondrial dysfunction has been supposed to play a crucial role in pathogenesis of diabetic peripheral neuropathy (DPN). The present study investigated the neuroprotective potential of quercetin, a natural APMK activator. Streptozotocin (STZ)-induced diabetic rats that developed DPN phenotype were orally administrated with quercetin (30 and 60 mg/kg, per day) for six weeks. The morphologic changes in the sciatic nerves (SN), the pathological structure of neurons in dorsal root ganglion (DRG), and the expressions of myelin proteins were assessed. The ATP content and the mitochondrial ultrastructure were measured. Furthermore, key proteins in AMPK/PGC-1α pathway were determined. As a result, quercetin administration at both two doses improved the paw withdrawal threshold, nerve conduction velocity, and the pathologic changes in SN and DRG of DPN rats. The expressions of myelin basic protein and myelin protein zero were also increased by quercetin. The oxidative stress, decreased ATP-generation, and morphological changes of mitochondria were corrected by quercetin. In-vitro study found that quercetin treatment significantly decreased the high-glucose induced generation of reactive oxygen species, as well as attenuated the mitochondrial morphologic injuries and oxidative DNA damages of RSC96 cells. Quercetin treatment promoted the expressions of phosphorylated AMPK, PGC-1α, SIRT1, NRF1, and TFAM under hyperglycemic state in vivo and in vitro. This study revealed that the neuroprotective effect of quercetin was mainly related to mitochondrial protection by activation of the AMPK/PGC-1α pathway for the first time, and proved quercetin as a potential therapeutic agent in management of diabetic neuropathy.